Does propofol and isoflurane protect the kidney against ischemia/reperfusion injury during transient hyperglycemia? - Carraretto, Antônio Roberto (2013)
PURPOSE: To study the effect of isoflurane (Iso) or propofol (Prop) anesthesia on renal ischemia/reperfusion injury (IRI) during transient hyperglycemia. METHODS: Thirty six rats were randomly assigned into six groups of six animals each: PHS (Sham-Prop=1mg.kg-1.min-1 + Hyperglycemia=2.5g.kg-1 of glucose solution administered intraperitoneally); HIS (Sham-Iso + Hyperglycemia); PHI (Prop + Hyperglycemia + Ischemia); IHI (Iso + Hyperglycemia + Ischemia); PI (Prop + Ischemia), and II (Iso + Ischemia). After 30 minutes of anesthesia induction, right nephrectomy was performed (all animals) and the left renal artery was clamped during 25 minutes (ischemia). The animals were sacrificed after 24 hours and blood collection (to dose creatinine) and left kidney removal were performed for histological analysis, and flow cytometry (FCM): percentage of initial apoptosis (APTi) and viable cells (VC). RESULTS: Serum creatinine (mg/dL) was statistically different in groups PHI (3.60±0.40) and IHI (3.23±1.08), p<0.05. Histological analysis was statistically different in groups PHI (4.0[4.0;5.0]) and IHI (4.5[4.0;5.0]), p<0.05. APTi percentage was statistically different in groups PHI (73.2±7.1), and IHI (48.1±14). VC percentage was statistically different in groups PHI (25.8±6.9) and IHI (38.5±9.2), p<0.05. CONCLUSIONS: Propofol and isoflurane showed the same level of protection against ischemia/reperfusion injury in the normoglycemic groups. Transient hyperglycemia is associated with an increase in IRI.